A method for preparing a high-nickel ternary positive electrode material, and the prepared high-nickel ternary positive electrode material and its use
Through spray coating and second sintering of weak acid organic coating liquid, the residual lithium problem in high-nickel ternary cathode materials is solved, the electrochemical performance is improved, the process flow is simplified, and the production cost is reduced.
Patent Information
- Application Number
- CN202310057080.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-01-16
AI Technical Summary
The existing high-nickel ternary cathode materials are prone to residual lithium after sintering, resulting in deterioration of battery performance and safety problems. The traditional water washing removal method is complex and damages the material structure and increases processing costs.
The weak acid organic coating liquid is spray-coated to form a coating layer, and then a second sintering is performed to remove residual lithium and improve electrochemical performance, simplify the process flow and reduce costs.
Effectively remove residual lithium, improve the electrochemical performance of high-nickel ternary cathode materials, simplify the process flow, reduce production costs, and avoid damage to the material structure by the water washing method.
Smart Images

Figure CN116143190B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium-ion batteries and relates to a method for preparing a high-nickel ternary positive electrode material and the prepared high-nickel ternary positive electrode material and its use. Background Art
[0002] The current lithium-ion batteries mainly include lithium manganese oxide batteries, lithium cobalt oxide batteries and ternary batteries. Ternary batteries have rapidly gained favor in the market due to their high energy density, good cycle life, environmental friendliness and low price, and are used in digital batteries, electric vehicles and other fields.
[0003] However, high-nickel ternary materials tend to have high residual lithium after the first sintering, which has a great impact on the battery. On the one hand, it will cause the viscosity of the positive electrode slurry to increase, resulting in coating difficulties. On the other hand, it will cause gas generation problems in the battery, causing battery expansion and performance deterioration. It will also cause safety problems, making it difficult for ternary power batteries to pass test conditions such as needle puncture and overcharging. Therefore, it is necessary to remove residual lithium from high-nickel materials;
[0004] The traditional solution is to first remove the residual lithium by water washing, and then perform mixed coating and sintering. For example, CN111653761A discloses a method for preparing a high-nickel positive electrode material improved by water washing, including: primary sintering, water washing, and secondary sintering. The water washing detergent is an aqueous solution containing additives, and the additives are at least one of acetic acid, hydrochloric acid, boric acid, carbamide, cobalt sulfate, sodium carbonate, sodium bicarbonate, sodium sulfite, and disodium hydrogen phosphate. The additive can effectively inhibit the release of structural lithium during the water washing process, while reducing the residual lithium content on the surface, protecting the material structure, and the additives remaining on the surface of the material will further react with the residual lithium released during the secondary sintering process, achieving the purpose of secondary removal of residual lithium, thereby effectively improving the capacity and cycle performance of the high-nickel positive electrode material. CN113249776B discloses a method for washing a high-nickel ternary positive electrode material, the method comprising preparing a high-nickel ternary positive electrode material matrix; mixing the high-nickel ternary positive electrode material matrix with water to obtain an electrolyte solution; and electrolyzing the electrolyte solution to remove residual alkali on the surface of the high-nickel ternary positive electrode material matrix.
[0005] The above technical solutions can produce a certain effect of inhibiting the precipitation of lattice lithium on the surface of the material, and thus remove a certain amount of residual lithium. However, the water washing method will destroy the structure of the material itself while removing the residual lithium, and the lithium in the material itself will also dissolve in the water, thereby causing lithium loss and structural damage. The process is complicated, with many steps and a long process, which makes the processing cost of high-nickel materials high, quality management difficult, and the material loss rate high.
[0006] Therefore, it is still necessary to develop a new technical solution for removing residual lithium to simplify the process and reduce damage to material properties. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a preparation method of a high-nickel ternary positive electrode material and the obtained high-nickel ternary positive electrode material and use, the preparation method comprising uniformly mixing a lithium source and a high-nickel ternary precursor, performing a first sintering to obtain a first sintering material; spray coating the first sintering material with a weakly acidic organic coating liquid to form a coating layer to obtain a residual lithium reduction coating material; and then performing a second sintering on the residual lithium reduction coating material to obtain a high-nickel ternary positive electrode material. The present invention uses a specific weakly acidic organic coating liquid to remove residual lithium while spraying and coating, and can directly perform a second sintering, which greatly shortens the process, and has a good effect of removing residual lithium, uniform coating, and the electrochemical performance of the obtained high-nickel ternary positive electrode material is improved.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a high-nickel ternary positive electrode material, the preparation method comprising the following steps:
[0010] S1: mixing the lithium source and the high-nickel ternary precursor uniformly, and performing a first sintering to obtain a first sintering material;
[0011] S2 uses a weakly acidic organic coating liquid to spray-coat the first sintered material obtained in step S1 to form a coating layer to obtain a reduced residual lithium coating material;
[0012] S3 performs a second sintering on the residual lithium reduction coating material described in step S2 to obtain a high-nickel ternary positive electrode material.
[0013] The preparation method of the present invention can avoid the influence of the water washing process on the material, and simplifies the traditional water washing-filtration-drying-mixed coating-sintering process into a spray coating + sintering process. During the coating process, a specific coating liquid is used to remove residual lithium, and then the coating and the substrate are combined to form a coating layer through the sintering process, which changes the way the traditional water washing process removes residual lithium and avoids excessive dissolution of lithium caused by contact between the positive electrode material and water. That is, the present scheme can avoid the phenomenon of structural lithium loss. In addition, the present scheme can achieve coating and residual lithium removal in one step, which greatly simplifies the process flow, improves production efficiency, reduces production costs, and has a good effect of removing residual lithium and uniform coating. The electrochemical performance of the obtained high-nickel ternary positive electrode material is improved.
[0014] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] As a preferred technical solution of the present invention, the molar ratio of the lithium source to the high-nickel ternary precursor in step S1 is (1.03-1.06):1, for example, 1.03:1, 1.035:1, 1.04:1, 1.045:1, 1.05:1, 1.055:1 or 1.06:1, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0016] Preferably, the lithium source in step S1 includes LiOH·H2O and / or Li2CO3.
[0017] Preferably, the high nickel ternary precursor in step S1 comprises Ni x Co y M (1-x-y) (OH)2, x≥0.8, y≤0.1, M includes any one of Al, Mn, Mg, Zn, Cu, Fe, Zr, W, Ta, Sr, Nb, Y or B, or a combination of at least two of them, typical but non-limiting examples of the combination include a combination of Al and Mn, a combination of Al and Mg, a combination of Al and Zn, a combination of Al and Cu, a combination of Al and Fe, a combination of Mn and Mg, a combination of Mn and Zn, a combination of Mn and Cu, a combination of Mn and Fe, a combination of Zn and Y, a combination of Zn and B, a combination of Y and B, a combination of Al and B, a combination of Ta and Sr, a combination of Sr and Nb, or a combination of Nb and Y.
[0018] Preferably, the temperature of the first sintering in step S1 is 700-900°C, for example, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C or 900°C, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0019] Preferably, the preparation method further comprises sequentially screening and demagnetizing the first sintered material obtained in step S1.
[0020] As a preferred technical solution of the present invention, the components of the weak acid organic coating solution in step S2 include a weak acid solvent.
[0021] Preferably, the weak acid solvent comprises any one of acetic acid, citric acid, maleic acid, lactic acid, oxalic acid or formic acid, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of acetic acid and citric acid, a combination of acetic acid and maleic acid, a combination of acetic acid and lactic acid, a combination of acetic acid and oxalic acid, a combination of acetic acid and formic acid, a combination of citric acid and maleic acid, a combination of citric acid and lactic acid, a combination of citric acid and oxalic acid, a combination of citric acid and formic acid, a combination of maleic acid and lactic acid, a combination of maleic acid and oxalic acid, a combination of maleic acid and formic acid, a combination of lactic acid and oxalic acid, a combination of lactic acid and formic acid, or a combination of oxalic acid and formic acid.
[0022] Preferably, the concentration of the weak acid solvent in the weak acid organic coating liquid is 0.001-0.1 mol / L, for example, 0.001 mol / L, 0.002 mol / L, 0.003 mol / L, 0.004 mol / L, 0.005 mol / L, 0.006 mol / L, 0.007 mol / L, 0.008 mol / L, 0.009 mol / L, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0023] The concentration of weak acid solvent has a great influence on the removal effect of residual lithium. On the one hand, too high a concentration will dissolve the nano-oxide capping agent, and on the other hand, it will cause the regional acidity of the solvent on the surface of the high-nickel ternary material to be too high, so that the matrix lithium also participates in the reaction, destroying the stability of the matrix Li content and the stability of the matrix layered structure; too low a concentration cannot completely remove the residual lithium and cannot achieve a good residual lithium removal effect. The concentration design of the weak acid solvent in this scheme is based on the residual lithium content of the high-nickel material, the spray speed and the material flow rate. Ultimately, it can achieve effective removal of residual lithium without damaging the high-nickel ternary material matrix.
[0024] Preferably, the weakly acidic organic coating solution in step S2 further comprises nano-oxide modified by a silane coupling agent.
[0025] Preferably, the solid content of the nano-oxide in the weakly acidic organic coating solution is 0.01 to 20 wt%, for example, 0.01 wt%, 0.03 wt%, 0.05 wt%, 0.075 wt%, 0.1 wt%, 0.3 wt%, 0.5 wt%, 0.75 wt%, 1 wt%, 3 wt%, 5 wt%, 7 wt%, 9 wt%, 12 wt%, 15 wt%, 17 wt%, 19 wt% or 20 wt%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0026] The present invention adds nano oxide modified by silane coupling agent to a specific weak acid organic coating liquid, and while removing residual lithium, the positive electrode base material is coated with the nano oxide, and a uniform nano oxide coating layer can be formed by air drying during the coating process. The nano oxide modified by the silane coupling agent, on the one hand, utilizes the hydrophobicity of the silane coupling agent, avoids the influence of the weak acid coating liquid on the nano oxide, and reduces the dissolution or agglomeration of the nano oxide caused by the weak acid coating liquid; on the other hand, utilizes the large surface tension between the silane coupling agents to increase the dispersibility of the nano oxide, and avoids the agglomeration of the nano oxide itself; the solid content of the nano oxide has an impact on the coating uniformity and the coating amount, and too high solid content makes the coated nano oxide unevenly distributed on the surface of the positive electrode base material, and too much coating on the surface of the positive electrode base material is not conducive to the subsequent lithium ion deintercalation and deteriorates the performance, while too low solid content makes the particles of some positive electrode base materials not well coated, and the material surface cannot be well protected.
[0027] Preferably, the silane coupling agent includes any one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane or γ-glycidylpropyltrimethoxysilane or a combination of at least two thereof, and typical but non-limiting examples of the combination include a combination of γ-aminopropyltriethoxysilane and vinyltriethoxysilane, a combination of vinyltriethoxysilane and γ-glycidylpropyltrimethoxysilane, or a combination of γ-glycidylpropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0028] Preferably, the composition of the nano oxide includes any one of zirconium oxide, aluminum oxide, magnesium oxide, titanium oxide, tungsten oxide, cobalt oxide or lanthanum oxide, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of zirconium oxide and aluminum oxide, a combination of zirconium oxide and magnesium oxide, a combination of zirconium oxide and titanium oxide, a combination of zirconium oxide and tungsten oxide, a combination of zirconium oxide and cobalt oxide, a combination of zirconium oxide and lanthanum oxide, a combination of aluminum oxide and magnesium oxide, a combination of aluminum oxide and titanium oxide, a combination of aluminum oxide and tungsten oxide, a combination of aluminum oxide and cobalt oxide, a combination of aluminum oxide and lanthanum oxide, a combination of magnesium oxide and titanium oxide, a combination of magnesium oxide and tungsten oxide, a combination of magnesium oxide and lanthanum oxide, a combination of titanium oxide and tungsten oxide, a combination of titanium oxide and cobalt oxide, a combination of titanium oxide and lanthanum oxide, a combination of tungsten oxide and cobalt oxide, a combination of tungsten oxide and lanthanum oxide, or a combination of cobalt oxide and lanthanum oxide.
[0029] Preferably, in the coating layer of step S2, the total content of metal elements derived from the nano-oxide is 500-5000ppm, for example, 500ppm, 800pm, 1100ppm, 1400ppm, 1700ppm, 2000ppm, 2300ppm, 2600ppm, 2900ppm, 3200ppm, 3500ppm, 3800ppm, 4100ppm, 4400ppm, 4700ppm or 5000ppm, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0030] As a preferred technical solution of the present invention, the device used for the spray coating in step S2 includes an air flow pulverizing device.
[0031] Preferably, the air flow pulverizing device comprises an air chamber (3), a rotary atomizer (5) extending into the interior of the air chamber (3), and an air port (4) circumferentially arranged on the inner wall of the air chamber (3), wherein the air inlet end of the air port (4) is connected to the air duct (2), and a discharge port is arranged at the top of the air chamber (3).
[0032] The spray drying in step S2 of the preparation method of the present invention can be carried out in an air flow pulverizing device, the rotary sprayer is used to spray out the weak acid organic coating liquid, the airway and the air port are used to introduce gas into the air chamber, which is used to drive the movement of the material in the air chamber, and simultaneously achieve the effect of air flow pulverizing and air drying; illustratively, the first sintered material obtained in step S1 is evenly sprayed with a certain concentration of weak acid organic coating liquid by a rotary sprayer in the air flow pulverizer. At this time, the weak acid solvent will react with the residual lithium on the surface of the first sintered material on the one hand, and then be quickly air-dried by the gas to avoid excessive reaction of the weak acid with the matrix material. On the other hand, the nano-oxide left after drying is evenly sprayed on the surface of the matrix material to form a coating layer, thereby achieving the one-step completion of removing the residual lithium and coating, greatly shortening the process.
[0033] As a preferred technical solution of the present invention, the rotary atomizer (5) comprises at least two nozzles (6).
[0034] Preferably, the nozzles (6) are arranged symmetrically.
[0035] Preferably, the number of the air ports (4) is 4 to 8, for example 4, 5, 6, 7 or 8.
[0036] Preferably, the air ports (4) are distributed at equal angles around the central axis of the air chamber (3).
[0037] Preferably, the gas outlet direction of each of the gas ports (4) is opposite to the rotation direction of the rotary atomizer (5).
[0038] Preferably, the angle between the air outlet direction of the air port (4) and the tangent direction of the air port (4) on the inner wall of the air chamber (3) is less than 90°, for example 88°, 84°, 80°, 70°, 50°, 30°, 10° or 5°, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0039] Preferably, the air channel (2) is an annular air channel, and the annular air channel is arranged on the outer wall of the air chamber (3) in a circumferential manner.
[0040] As a preferred technical solution of the present invention, the spray coating in step S2 is carried out at a pressure of 0.1 to 5 MPa, for example, 0.1 MPa, 0.4 MPa, 0.7 MPa, 1 MPa, 1.3 MPa, 1.6 MPa, 1.9 MPa, 2.2 MPa, 2.5 MPa, 2.8 MPa, 3.1 MPa, 3.4 MPa, 3.7 MPa, 4 MPa, 4.3 MPa, 4.6 MPa, 4.8 MPa or 5 MPa, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0041] Preferably, when performing the spray coating in step S2, the spraying speed of the weakly acidic organic coating liquid is 1 mL / min to 5 L / min, for example, 1 mL / min, 5 mL / min, 10 mL / min, 25 mL / min, 50 mL / min, 75 mL / min, 100 mL / min, 150 mL / min, 200 mL / min, 350 mL / min, 500 mL / min, 750 mL / min, 900 mL / min, 1 L / min n, 1.25L / min, 1.5L / min, 1.75L / min, 2L / min, 2.25L / min, 2.5L / min, 2.75L / min, 3L / min, 3.25L / min, 3.5L / min, 3.75L / min, 4L / min, 4.25L / min, 4.5L / min, 4.75L / min or 5L / min, but are not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0042] Preferably, in step S2, drying is performed by using dry gas for exhaust drying during the spray coating.
[0043] Preferably, the drying gas comprises air.
[0044] Preferably, the temperature of the exhaust drying is 100-500°C, for example 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0045] As a preferred technical solution of the present invention, the temperature of the second sintering in step S3 is 300-900°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0046] Preferably, the preparation method further comprises screening, demagnetizing and drying the high-nickel ternary positive electrode material obtained in step S3 in sequence.
[0047] In a second aspect, the present invention provides a high-nickel ternary positive electrode material prepared by the preparation method described in the first aspect.
[0048] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate contains the high-nickel ternary positive electrode material described in the second aspect.
[0049] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in the third aspect.
[0050] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0051] The preparation method of the present invention can avoid the influence of the water washing process on the material, simplify the traditional water washing-filtration-drying-mixed coating-sintering process to spray coating + sintering process, use a specific coating liquid to remove residual lithium during the coating process, and then combine the coating and the substrate to form a coating layer through the sintering process, change the traditional water washing process to remove residual lithium, and achieve coating and removal of residual lithium in one step, greatly simplify the process flow, and improve production efficiency. And the effect of removing residual lithium is good, the coating is uniform, and the electrochemical performance of the obtained high-nickel ternary positive electrode material is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a front schematic diagram of the airflow pulverizing device used in the spray coating of the embodiment and the comparative example;
[0053] Figure 2 1 is a schematic top view of the airflow pulverizing device used in the spray coating of the embodiment and the comparative example;
[0054] Figure 3 This is a scanning electron microscope test image of the high-nickel ternary positive electrode material obtained in Example 1;
[0055] In the figure: 1-air inlet, 2-air duct, 3-air chamber, 4-air port, 5-sprayer, 6-nozzle. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] Figure 1 and Figure 2 Schematic diagram of the airflow pulverizing device used in the spray coating of the embodiment and the comparative example, the airflow pulverizing device comprises an air chamber 3, and a discharge port is arranged at the top of the air chamber 3;
[0058] The air flow pulverizing device further includes a rotary sprayer 5 extending into the air chamber 3 and arranged at the central axis position of the air chamber, and two nozzles 6 are symmetrically arranged on the rotary sprayer 5. When viewed from the top, the rotary sprayer rotates counterclockwise to spray the weakly acidic organic coating liquid in the air chamber 3;
[0059] The air flow pulverizing device also includes six air ports 4 circumferentially arranged on the inner wall of the air chamber 3, and the angle between two connected air ports 4 around the central axis of the air chamber 3 is 60°; when viewed from the top, the air outlet direction of each air port 4 is clockwise, which is opposite to the rotation direction of the rotary sprayer 5, and the angle between the air outlet direction of the air port 4 and the tangent direction of the air port 4 on the inner wall of the air chamber 3 is 30°; the air inlet end of the air port 4 is connected to the airway 2, and the airway 2 is an annular airway, which is arranged around the outer wall of the air chamber 3, and the air inlet 1 of the airway 2 is connected to a compressed air source.
[0060] Example 1
[0061] This embodiment provides a method for preparing a high-nickel ternary positive electrode material, the preparation method comprising the following steps:
[0062] S1 LiOH·H2O and Ni were mixed in a molar ratio of 1.04:1 0.9 Co 0.05 Mn 0.05 (OH)2 is mixed evenly, first sintered in a kiln at 800°C, and then crushed, sieved and demagnetized in sequence to obtain a first sintered material;
[0063] S2: conveying the first sintered material obtained in step (1) to an air flow pulverizing device, setting the pressure of the air injected through the air port to 3 MPa and the temperature to 300° C.; introducing a weak acid organic coating liquid into a rotary sprayer, wherein the weak acid organic coating liquid contains 0.05 mol / L acetic acid and nano zirconium oxide coated with γ-aminopropyltriethoxysilane, and the solid content of the nano zirconium oxide in the weak acid organic coating liquid is 10 wt %. The weak acid organic coating liquid is sprayed through a nozzle at a speed of 3 L / min to spray-coat the first sintered material, so that the acetic acid reacts with the residual lithium on the surface, and after air drying, a uniform coating layer composed of nano zirconium oxide is formed on the surface of the first sintered material, thereby obtaining a residual lithium-reducing coating material;
[0064] S3 outputs the reduced-lithium coating material from the airflow pulverizer into a sagger, performs a second sintering on the reduced-lithium coating material at 500° C., and obtains a high-nickel ternary positive electrode material after screening, demagnetization and drying.
[0065] Example 2
[0066] This embodiment provides a method for preparing a high-nickel ternary positive electrode material, the preparation method comprising the following steps:
[0067] S1 LiOH·H2O and Ni were mixed in a molar ratio of 1.03:1 0.8 Co 0.1 Al 0.1 (OH)2 is mixed evenly, first sintered in a kiln at 700°C, and then crushed, sieved and demagnetized in sequence to obtain a first sintered material;
[0068] S2: conveying the first sintered material obtained in step (1) to an air flow pulverizing device, setting the pressure of the air sprayed into the air port to 0.1 MPa and the temperature to 100° C.; introducing a weak acid organic coating liquid into a rotary sprayer, wherein the weak acid organic coating liquid contains 0.1 mol / L citric acid and nano-alumina coated with vinyltriethoxysilane, and the solid content of the nano-alumina in the weak acid organic coating liquid is 0.01 wt %. The weak acid organic coating liquid is sprayed through a nozzle at a speed of 5 L / min to spray-coat the first sintered material, so that the citric acid reacts with the residual lithium on the surface to form a uniform coating layer composed of nano-alumina on the surface of the first sintered material after air drying, thereby obtaining a residual lithium-reducing coating material;
[0069] S3 outputs the reduced lithium coating material from the air flow mill into a sagger, performs a second sintering on the reduced lithium coating material at 900° C., and obtains a high-nickel ternary positive electrode material after screening, demagnetization and drying.
[0070] Example 3
[0071] This embodiment provides a method for preparing a high-nickel ternary positive electrode material, the preparation method comprising the following steps:
[0072] S1 Li2CO3 and Ni were mixed in a molar ratio of 1.05:1 0.92 Co 0.04 Mn 0.03 Y 0.01 (OH)2 is mixed evenly, first sintered in a kiln at 900°C, and then crushed, sieved and demagnetized in sequence to obtain a first sintered material;
[0073] S2: conveying the first sintered material obtained in step (1) to an air flow pulverizing device, setting the air pressure of the air injected into the air port to 5 MPa and the temperature to 500° C.; introducing a weak acid organic coating liquid into a rotary sprayer, wherein the weak acid organic coating liquid contains 0.001 mol / L of maleic acid and nano-titanium oxide coated with γ-glycidyl ether propyl trimethoxysilane, and the solid content of the nano-titanium oxide in the weak acid organic coating liquid is 20 wt %. The weak acid organic coating liquid is sprayed through a nozzle at a speed of 1 mL / min to spray-coat the first sintered material, so that the maleic acid reacts with the residual lithium on the surface to form a uniform coating layer composed of nano-titanium oxide on the surface of the first sintered material after air drying, thereby obtaining a residual lithium-reducing coating material;
[0074] S3 outputs the reduced-lithium coating material from the airflow pulverizer into a sagger, performs a second sintering on the reduced-lithium coating material at 500° C., and obtains a high-nickel ternary positive electrode material after screening, demagnetization and drying.
[0075] Example 4
[0076] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except for adjusting the temperature of the air in step (2) from 300° C. to 70° C., other conditions in the preparation method are exactly the same as those in Example 1.
[0077] Example 5
[0078] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except for adjusting the temperature of the air in step (2) from 300° C. to 100° C., other conditions in the preparation method are exactly the same as those in Example 1.
[0079] Example 6
[0080] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except for adjusting the temperature of the air in step (2) from 300° C. to 500° C., other conditions in the preparation method are exactly the same as those in Example 1.
[0081] Example 7
[0082] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except for adjusting the temperature of the air in step (2) from 300° C. to 530° C., other conditions in the preparation method are exactly the same as those in Example 1.
[0083] Example 8
[0084] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except that the concentration of acetic acid in step (2) is adjusted from 0.05 mol / L to 0.001 mol / L, other conditions are exactly the same as those in Example 1.
[0085] Example 9
[0086] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except for adjusting the acetic acid concentration in step (2) from 0.05 mol / L to 0.005 mol / L, other conditions are exactly the same as those in Example 1.
[0087] Example 10
[0088] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except for adjusting the acetic acid concentration in step (2) from 0.05 mol / L to 0.03 mol / L, other conditions in the preparation method are exactly the same as those in Example 1.
[0089] Embodiment 11
[0090] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except that the concentration of acetic acid in step (2) is adjusted from 0.05 mol / L to 0.1 mol / L, other conditions are exactly the same as those in Example 1.
[0091] Example 12
[0092] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. Except for adjusting the acetic acid concentration in step (2) from 0.05 mol / L to 0.12 mol / L, other conditions in the preparation method are exactly the same as those in Example 1.
[0093] Embodiment 13
[0094] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The weakly acidic organic coating liquid used in step (2) of the preparation method is composed of only 0.05 mol / L acetic acid and does not contain nano-zirconium oxide coated with γ-aminopropyltriethoxysilane, so that no coating layer is formed on the surface of the first sintered material. Other conditions are exactly the same as those in Example 1.
[0095] Embodiment 14
[0096] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The preparation method is exactly the same as that of Example 1, except that the solid content of the nano-zirconium oxide in the weakly acidic organic coating solution in step (2) is adjusted from 10wt% to 0.01wt%.
[0097] Embodiment 15
[0098] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The preparation method is exactly the same as that of Example 1 except that the solid content of the nano-zirconium oxide in the weakly acidic organic coating solution in step (2) is adjusted from 10wt% to 0.1wt%.
[0099] Example 16
[0100] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The preparation method is exactly the same as that of Example 1 except that the solid content of the nano-zirconium oxide in the weakly acidic organic coating solution in step (2) is adjusted from 10wt% to 1wt%.
[0101] Embodiment 17
[0102] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The preparation method is exactly the same as that of Example 1 except that the solid content of the nano-zirconium oxide in the weakly acidic organic coating solution in step (2) is adjusted from 10wt% to 5wt%.
[0103] Embodiment 18
[0104] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The preparation method is exactly the same as that of Example 1 except that the solid content of the nano-zirconium oxide in the weakly acidic organic coating solution in step (2) is adjusted from 10wt% to 20wt%.
[0105] Embodiment 19
[0106] This embodiment provides a method for preparing a high-nickel ternary positive electrode material. The preparation method is exactly the same as that of Example 1 except that the solid content of the nano-zirconium oxide in the weakly acidic organic coating solution in step (2) is adjusted from 10wt% to 22wt%.
[0107] Comparative Example 1
[0108] This comparative example provides a method for preparing a high-nickel ternary positive electrode material. The weakly acidic organic coating liquid used in step (2) of the preparation method is composed only of nano-zirconium oxide coated with γ-aminopropyltriethoxysilane and does not contain acetic acid. Other conditions are exactly the same as those in Example 1.
[0109] Comparative Example 2
[0110] This comparative example provides a method for preparing a high-nickel ternary positive electrode material. The preparation method does not use a weakly acidic organic coating solution in step (2), and other conditions are exactly the same as those in Example 1.
[0111] Comparative Example 3
[0112] This comparative example provides a method for preparing a high-nickel ternary positive electrode material, the preparation method comprising the following steps:
[0113] S1 LiOH·H2O and Ni were mixed in a molar ratio of 1.04:1 0.9 Co 0.05 Mn 0.05 (OH)2 is mixed evenly, first sintered in a kiln at 800°C, and then crushed, sieved and demagnetized in sequence to obtain a first sintered material;
[0114] S2: uniformly stirring the first sintered material obtained in step (1) with a weakly acidic organic coating liquid, wherein the weakly acidic organic coating liquid contains 0.05 mol / L acetic acid and nano-zirconium oxide coated with γ-aminopropyltriethoxysilane, wherein the solid content of the nano-zirconium oxide in the weakly acidic organic coating liquid is 10 wt %, and drying at 300° C. to obtain a stirred material;
[0115] S3 performs a second sintering on the stirred material in step S2 at 800° C., and obtains a high-nickel ternary positive electrode material after screening, demagnetization and drying.
[0116] The scanning electron microscope was used to photograph Example 1, and the results are as follows: Figure 3 As shown in the figure, it can be seen that the point-shaped coating is evenly distributed on the surface of the particles without agglomeration, and is well combined with the matrix material, which will play a good coating role.
[0117] The high-nickel ternary positive electrode materials obtained in the examples and comparative examples were subjected to potentiometric titration. 10 g of the sample was dissolved in 100 mL of distilled water, stirred at 500 r / min for 15 min, 1 mL was added to a 100 mL beaker, 50 mL of distilled water was added, and the solution was placed on a titrator. The potentiometric titrator was turned on, and 0.001 mol / L standard hydrochloric acid solution was used. V was recorded when the pH was 4-5.0, and the residual lithium content was calculated. The results are listed in Table 1.
[0118] The high nickel ternary positive electrode material obtained in the embodiment and the comparative example was mixed with Super P and PVDF in a mass ratio of 95:2.5:2.5, with NMP as the solvent to prepare a slurry with a solid content of 70%. The slurry was then coated and dried to make positive electrode sheets and then assembled into button cells. The electrical properties of the materials were tested, and the results are listed in Table 1.
[0119] Table 1
[0120]
[0121] It can be seen from Table 1 that:
[0122] By comparing Example 1 with Examples 4-7, it can be seen that the spray drying temperature affects the reaction time of the weak acid coating liquid and the residual lithium. A lower spray drying temperature allows the weak acid and the residual lithium to react deeply and destroy the matrix, resulting in a lower residual lithium value. However, the matrix is destroyed and the cycle life is reduced. However, an excessively high spray drying temperature causes the weak acid coating liquid and the residual lithium to have no time to react, resulting in a higher residual lithium value and the cycle life is also affected.
[0123] By comparing Example 1 with Examples 8-12 and Comparative Example 1, it can be seen that the concentration of weak acid affects the amount of residual lithium removed. A lower weak acid concentration removes less residual lithium, resulting in a higher amount of residual lithium and a reduced cycle life. An excessively high weak acid concentration can remove most of the residual lithium, but there is also a risk of reaction with the matrix, which will lead to a reduction in cycle performance. Although no weak acid is added to the coating solution in Comparative Example 1, a portion of the residual lithium can be removed, but there is no obvious effect on improving the cycle performance.
[0124] By comparing Example 1 with Example 13, it can be seen that without adding the silane coupling agent, the nano-oxide will be partially dissolved by the weakly acidic solvent, thereby failing to play a coating role and causing poor cycle performance.
[0125] By comparing Example 1 with Examples 14-19 and Comparative Example 2, it can be seen that the solid content of the nano oxide affects the coating element content on the one hand, and also affects the cycle performance on the other hand. Too low a solid content leads to a very low coating element content, and the cycle performance cannot be improved; while too high a solid content causes the coating elements to agglomerate and cannot be well dispersed on the protective interface, but instead forms a thicker impedance layer, resulting in increased impedance and thus deterioration of the cycle performance; Comparative Example 2 does not use a coating liquid, so the material is not coated and modified, the residual lithium is high, and the cycle performance is poor.
[0126] By comparing Example 1 with Comparative Example 3, it can be seen that when the coating is performed without spraying and the conventional mixing method is used, although the coating element can be added, the uniform distribution of the coating element cannot be guaranteed, and the residual lithium cannot be removed, resulting in poor cycle performance.
[0127] In summary, taking into account the spray drying temperature, using a certain concentration of weak acid coating liquid, and a nano-oxide coating agent with a certain solid content will help reduce residual lithium and improve cycle performance.
[0128] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0129] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0130] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0131] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a high-nickel ternary positive electrode material, characterized in that: The preparation method comprises the following steps: S1. Evenly mix the lithium source and the high-nickel ternary precursor, and perform a first sintering to obtain a first sintered material; S2 spray-coating the first sintered material obtained in step S1 with a weakly acidic organic coating liquid to form a coating layer to obtain a reduced residual lithium coating material; The components of the weak acid type organic coating liquid include a weak acid solvent and a nano oxide modified by a silane coupling agent; The weak acid solvent includes any one of acetic acid, citric acid, maleic acid, lactic acid, oxalic acid or formic acid, or a combination of at least two thereof; The silane coupling agent includes any one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane or γ-glycidyl ether propyltrimethoxysilane or a combination of at least two thereof; The spray coating uses dry gas for exhaust drying; S3: performing a second sintering on the residual lithium reduction coating material described in step S2 to obtain a high-nickel ternary positive electrode material.
2. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The molar ratio of the lithium source to the high-nickel ternary precursor in step S1 is (1.03~1.06):
1.
3. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The lithium source in step S1 includes LiOH·H2O and / or Li2CO3.
4. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The high nickel ternary precursor in step S1 includes Ni x Co y M (1-x-y) (OH)2, x≥0.8, y≤0.1, M includes any one of Al, Mn, Mg, Zn, Cu, Fe, Zr, W, Ta, Sr, Nb, Y or B or a combination of at least two of them.
5. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: In step S1, the temperature of the first sintering is 700-900°C.
6. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The preparation method further includes sequentially screening and demagnetizing the first sintered material obtained in step S1.
7. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The concentration of the weak acid solvent in the weak acid organic coating solution is 0.001-0.1 mol / L.
8. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The solid content of the nano-oxide in the weakly acidic organic coating solution is 0.01-20 wt %.
9. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The components of the nano-oxide include any one of zirconium oxide, aluminum oxide, magnesium oxide, titanium oxide, tungsten oxide, cobalt oxide or lanthanum oxide, or a combination of at least two thereof.
10. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: In the coating layer of step S2, the total content of metal elements derived from the nano-oxide is 500-5000 ppm.
11. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The device used for the spray coating in step S2 includes an air flow pulverizing device.
12. The method for preparing a high-nickel ternary positive electrode material according to claim 11, characterized in that: The air flow pulverizing device comprises an air chamber (3), a rotary atomizer (5) extending into the interior of the air chamber (3), and an air port (4) circumferentially arranged on the inner wall of the air chamber (3), wherein an air inlet end of the air port (4) is connected to an air passage (2), and a discharge port is arranged at the top of the air chamber (3).
13. The method for preparing a high-nickel ternary positive electrode material according to claim 12, characterized in that: The rotary atomizer (5) comprises at least two nozzles (6).
14. The method for preparing a high-nickel ternary positive electrode material according to claim 13, characterized in that: The nozzles (6) are arranged symmetrically.
15. The method for preparing a high-nickel ternary positive electrode material according to claim 12, characterized in that: The number of the air ports (4) is 4 to 8.
16. The method for preparing a high-nickel ternary positive electrode material according to claim 12, characterized in that: The air ports (4) are distributed at equal angles around the central axis of the air chamber (3).
17. The method for preparing a high-nickel ternary positive electrode material according to claim 12, characterized in that: The gas outlet direction of each gas port (4) is opposite to the rotation direction of the rotary atomizer (5).
18. The method for preparing a high-nickel ternary positive electrode material according to claim 12, characterized in that: The angle between the gas outlet direction of the gas port (4) and the tangent direction of the gas port (4) on the inner wall of the gas chamber (3) is less than 90°.
19. The method for preparing a high-nickel ternary positive electrode material according to claim 12, characterized in that: The air passage (2) is an annular air passage, and the annular air passage is arranged around the outer wall of the air chamber (3).
20. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The spray coating in step S2 is performed at a pressure of 0.1-5 MPa.
21. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: When performing the spray coating in step S2, the spraying rate of the weakly acidic organic coating liquid is 1 mL / min to 5 L / min.
22. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The drying gas includes air.
23. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The temperature of the exhaust drying is 100-500°C.
24. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: In step S3, the second sintering temperature is 300-900°C.
25. The method for preparing a high-nickel ternary positive electrode material according to claim 1, characterized in that: The preparation method further includes sequentially screening, demagnetizing and drying the high-nickel ternary positive electrode material obtained in step S3.
26. A high-nickel ternary positive electrode material prepared by the preparation method according to any one of claims 1 to 25.
27. A positive electrode plate, characterized in that: The positive electrode plate contains the high-nickel ternary positive electrode material as described in claim 26.
28. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 27.
